CARBON FOOTPRINT FROM THE SALE OF THE FRUIT AND THE PRODUCTION OF AGUAJE (Mauritia flexuosa L. f) DRINKS AND ICE CREAMS IN THE DEPARTMENT OF UCAYALI, PERU - GARCÍA-SORIA, Diego Gonzalo (2020)
The carbon footprint of the sale of the fruit and the production beverages and ice creams of aguaje was estimated. The study was carried out in the city of Pucallpa, Callería district, where the products are sold, and in the Túpac Amaru hamlet, Manantay district where the fruits are extracted, which are both located in the province of Coronel Portillo, department of Ucayali. The carbon footprint of all the phases of the commercialization of the fruits, and the production of drinks and aguaje ice creams were studied, for which information on their CO2 emissions was collected through surveys carried out to 46 producers. It was estimated that the carbon footprint of the sale of the aguaje fruit was 0.07031 KgCO2eq for each fruit obtained by felling the palm tree and placed in the retail centers of the city of Pucallpa. Emissions were lower when the fruit was harvested without cutting down the palm tree, reducing the carbon footprint by 83.53%, that is, emitting only 0.001158 KgCO2eq per aguaje fruit. The carbon footprints of a 250 ml glass of aguaje drink and the 75 ml aguaje ice cream were higher, obtaining values ​​of 0.89317 and 0.0887 KgCO2eq, respectively. Therefore, there is a need to promote the use of the sustainable use of aguaje using technology that allows the palm trees to be ascended without having to cut them down. This technology must be accepted by the inhabitants who carry out the extraction and favored by the consumers.